syms ga(y) gb(y) gc(x) gd(x) f(x,y);
z=(-(h^2)*(f(xi(1),yj(m-1)))+ga(yj(m-1))+lambda*gd(xi(1))+lambda*wij(1,m-2)+wij(2,m-1))/mu;
z = (-h^2*f(xi(i),yj(m-1))+lambda*gd(xi(i))+wij(i-1,m-1)+wij(i+1,m-1)+lambda*wij(i,m-2))/mu;
if abs(wij(i,m-1)-z)>NORM
NORM = abs(wij(i,m-1)-z);
z=(-h^2*f(xi(n-1),yj(m-1))+gb(yj(m-1))+lambda*gd(xi(n-1))+wij(n-2,m-1)+lambda*wij(n-1,m-2))/mu;
if abs (wij(n-1,m-1)-z) > NORM
NORM = abs (wij(n-1,m-1)-z);
z=(-(h^2)*f(xi(1),yj(j))+ga(yj(j))+lambda*wij(1,j+1)+lambda*wij(1,j-1)+wij(2,j))/mu;
z=(-(h^2)*f(xi(i),yj(j))+wij(i-1,j)+lambda*wij(i,j+1)+wij(i+1,j)+lambda*wij(i,j-1))/mu;
z=(-h^2*f(xi(n-1),yj(j))+gb(yj(j))+wij(n-2,j)+lambda*wij(n-1,j+1)+lambda*wij(n-1,j-1))/mu;
if abs(wij(n-1,j)-z)>NORM
z = (-h^2*f(xi(1),yj(1))+ga(yj(1))+lambda*gc(xi(1))+lambda*wij(1,2)+wij(2,1))/mu;
if abs(wij(1,1)-z) > NORM
z = (-h^2*f(xi(i),yj(1))+lambda*gc(xi(i))+wij(i-1,1)+lambda*wij(i,2)+wij(i+1,1))/mu;
z=(-h^2*f(xi(n-1),yj(1))+gb(yj(1))+lambda*gc(xi(n-1))+wij(n-2,1)+lambda*wij(n-1,2))/mu;
if abs (wij(n-1,1)-z) > NORM
NORM= abs(wij(n-1,1)-z) ;
disp(" "+double(xi(i))+" "+double(yj(j))+" "+double(wij(i,j)))